EMPOWERMENT OF PROBLEM-SOLVING SKILLS THROUGH THE INVESTIGATION THROUGH COOPERATIVE PROBLEM SOLVING (ITCPS) MODEL IN LIVING OF CLASSIFICATION MATERIALS - Bayu Rizki Prasadityo; Mohammad Masykuri; Budi Utami (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2023)
Problem-solving is a thinking skill related to how students can find a solution to a problem. Problem-solving skills play an essential role in forming a person who is responsible for decisions taken and faces challenges. This study aims to determine the effect of the Investigations Through Cooperative Problem Solving (ITCPS) model on empowering problem-solving skills in the Classification of Living Things material. This study used a quasi-experimental pretest-posttest control group design. This research was conducted in semester 1 at one of Junior High School in Karanganyar. Random sampling technique to determine control class and experimental class in seventh grade students namely 7B and 7C. Data collection used a problem-solving skills test instrument and limited interviews. Analysis used independent sample t-test using SPSS software and N-Gain Score. The results showed that the ITCPS learning model affected empowering problem-solving skills with a Sig. (2-tailed) of 0.000 <0.05 and the N-Gain Score test of 53.18 (medium increase). This research implies that the ITCPS learning model with group-based problem investigation can empower problem-solving skills.